Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

Above-ground biomass and productivity in the Montado: From herbaceous to shrub dominated communities - Castro, H.; Freitas, H. (Journal of Arid Environments, 2009)
Our study was focused on the effect of abandonment on above-ground biomass and net primary productivity (ANPP) in a Montado in Southern Portugal. The Montado has a long history of human management and control of invasion by shrubs is achieved by clearing, ploughing and grazing. When these cease, it is invaded by Mediterranean matorral species. We hypothesized that the change in life form dominance would affect both biomass and productivity, but while the total biomass was expected to increase, the effects on ANPP were less clear. We tested our hypothesis by determining above-ground biomass and ANPP along a gradient of decreasing land use intensity, ranging from extensive grazing to 20 years of abandonment. Above-ground biomass increased with abandonment, which was related with the increase in shrub cover. In addition, we found a decrease in herbaceous ANPP that was more than compensated by an increase in shrub ANPP in plots abandoned for longer time, resulting in a signiﬁcant increase in total ANPP. This increase was strongly related with the increase in the cover of Cistus ladanifer, a pioneer species that colonises degraded areas and forms one of the ﬁrst stages of succession of woody communities.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Land use change; Life form; Mediterranean; Secondary succession; semi-arid

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid

Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) response to different soil preparation techniques applied to forestation in abandoned farmland - Bocio, Inmaculada; Navarro, Francisco Bruno; Ripoll, María Angeles; Jiménez, María Noelia; Simón, Estanislao De (Ann. For. Sci., 2004)
This paper evaluates the effectiveness of several soil preparation procedures in forestation establishment and development in localized farmland, within a territory in ombroclimatic transition between dry and semi-arid, located in Granada, southeastern Spain. An experiment in the forestation of Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) was set up, in which 8 different soil preparation techniques were used. The survival, total height and basal diameter of the plantation was monitored over a 5-year period (1996-2000). The statistical analysis of these parameters evidenced highly significant differences in the overall behaviour of the two sample forest species, related to changes in the prevailing environmental conditions in these territories and the type of soil preparation procedure applied. The overall results obtained for the three parameters analysed show the effectiveness of using backhoes for pit planting and linear rippering with a hydraulic structure to captures runoffs, in comparison to other preparations. Areal soil preparations, in particular, are not recommended.
Keywords: forestation; semi-arid; soil preparation

Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) response to different soil preparation techniques applied to forestation in abandoned farmland - Bocio, Inmaculada; Navarro, Francisco Bruno; Ripoll, María Angeles; Jiménez, María Noelia; Simón, Estanislao De (Ann. For. Sci., 2004)
This paper evaluates the effectiveness of several soil preparation procedures in forestation establishment and development in localized farmland, within a territory in ombroclimatic transition between dry and semi-arid, located in Granada, southeastern Spain. An experiment in the forestation of Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) was set up, in which 8 different soil preparation techniques were used. The survival, total height and basal diameter of the plantation was monitored over a 5-year period (1996-2000). The statistical analysis of these parameters evidenced highly significant differences in the overall behaviour of the two sample forest species, related to changes in the prevailing environmental conditions in these territories and the type of soil preparation procedure applied. The overall results obtained for the three parameters analysed show the effectiveness of using backhoes for pit planting and linear rippering with a hydraulic structure to captures runoffs, in comparison to other preparations. Areal soil preparations, in particular, are not recommended.
Keywords: forestation; semi-arid; soil preparation